Knowledge and Awareness about Aggravating Factors of the Peptic Ulcer Disease: A Cross-Sectional Study - Khaity, Abdulrhman; Albakri, Khaled; Taha, Ruaa E.; Ali Yousif Abd Alla, Ahmed Mohammed (International Journal of Medical Students, 2023)
Background: Peptic ulcer disease is a gastrointestinal disorder due to the imbalance between the defense mechanism and gastric acid secretion. It affects 5-10% of the population worldwide and induces eight million deaths every year globally. In Sudan, this disease represents one of the major health problems. Limited studies have shown the knowledge level of Sudanese about aggravating factors of Peptic ulcer disease, which lead to more prevalent complications. Therefore, this study aimed to assess awareness about aggravating factors of peptic ulcer disease among the population of Khartoum state, Sudan. Method: A descriptive cross-sectional study targeted the general population in Khartoum state during the period from January to June 2022. We used an online survey form to collect data from the study population. The distribution of the questionnaire was done via social media tools. We analyzed the data using SPSS Software version 26. Results: The study included 398 participants, 40.7% of them male and 59.3% female, with mean age equal to 24.9 (SD=8.9), and a range between (18-64). Most of the participants (77.1%) were unmarried and (89.2%) were educated. The type of food was the most known risk factor (79.1%) and the weather changes were the least known risk factor (8.5%) that have effects on peptic ulcers. There also was a significant difference between educated and non-educated people based on the awareness of peptic ulcer risk factors, as the second was higher (p>0.000). Furthermore, people with peptic ulcers and people who have one or more members of their family with peptic ulcers scored more than nonpatients and those who did not have (p>0.000, p= 0.04; respectively). Conclusion: In conclusion, awareness about aggravating factors of peptic ulcers was variable among the population in Khartoum state. Our study findings revealed a high knowledge effect of type of food, helicobacter pylori, analgesic medications, drinking coffee, smoking, and social stress of the majority population. As for other factors, weather changes, genetic factors, and body weight were associated with a poor level of awareness. Lastly, these results need to be affirmed by furthermore research with a large sample among the general population in different regions in Sudan.